A Comparative Study of Bivalirudin Plus Clopidogrel versus Bivalirudin Plus Prasugrel in Primary Angioplasty Using Propensity Score Matching. (18th August 2013) - DÍAZ DE LA LLERA, LUIS S.; CUBERO GÓMEZ, JOSÉ‐M.; RANGEL, DIEGO; PAREJO, JUAN; ACOSTA, JUAN; FERNÁNDEZ‐CISNAL, AGUSTÍN; ZAFRA, FRANCISCO; BENEZET, JAVIER
Abstract Introduction and Objectives In primary angioplasty, bivalirudin is superior to treatment with heparin plus glycoprotein inhibitors for reducing cardiovascular events, although bivalirudin increases the risk of stent thrombosis. Our hypothesis is that the use of prasugrel plus bivalirudin in primary angioplasty would reduce stent thrombosis and cardiovascular events. Method Consecutive patients with acute ST‐segment elevation myocardial infarction who were treated by primary angioplasty within 12 hours of the onset of symptoms received bivalirudin plus clopidogrel (Group A) or bivalirudin plus prasugrel (Group B). We compared the groups using propensity score matching. The combined end‐point was cardiac death, thrombosis, acute myocardial infarction, and cerebrovascular accident at 30 days. Results We assessed 168 patients. The approach was preferentially radial (95.7%). No differences in baseline characteristics were observed between Groups A (n = 70) and B (n = 70). The total mortality and rate of major bleeding complications at 30 days were 0% for both of the groups. The rate of acute and subacute thrombosis was 4.3% in Group A and 0% in Group B (P = 0.08). We observed an increased rate of events in Group A (5.7%) versus Group B (0%) (P = 0.042). Conclusions The administration of bivalirudin plus prasugrel in primary percutaneous coronary intervention reduces cardiovascular effects compared to bivalirudin plus clopidogrel without increasing major bleeding complications during the first 30 days following primary angioplasty performed with a preferentially radial approach. (J Interven Cardiol 2013;26:463‐469)